2019
DOI: 10.1177/0734282919846030
|View full text |Cite
|
Sign up to set email alerts
|

The Big Three Perfectionism Scale: Factor Structure and Measurement Invariance in a Turkish Sample

Abstract: Perfectionism is a crucial concept in psychology as perfectionism has been found to be related to many important factors affecting daily and academic life. Many researchers have tried to measure perfectionism since 1980. Following an extensive literature review, Smith, Saklofske, Stoeber, and Sherry developed a new perfectionism scale called Big Three Perfectionism Scale (BTPS). The present study addressed the validation study of the BTPS in Turkish sample. The factor structure of the BTPS and measurement inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…The correlations between narcissistic perfectionism, i.e., the belief that one is superior to others and should be treated as such [ 88 ], and burnout showed a lower magnitude, compared to other perfectionism dimensions in our study, as well as to what we would expect using the trait narcissism, based on previous literature [ 89 , 90 , 91 ], indicating a less pernicious nature of the narcissistic type of perfectionism, which only becomes apparent when the demands from the environment are too stressful and prolonged over time, thus jeopardizing the individual’s subjective ability to be perfect.…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between narcissistic perfectionism, i.e., the belief that one is superior to others and should be treated as such [ 88 ], and burnout showed a lower magnitude, compared to other perfectionism dimensions in our study, as well as to what we would expect using the trait narcissism, based on previous literature [ 89 , 90 , 91 ], indicating a less pernicious nature of the narcissistic type of perfectionism, which only becomes apparent when the demands from the environment are too stressful and prolonged over time, thus jeopardizing the individual’s subjective ability to be perfect.…”
Section: Discussionmentioning
confidence: 99%
“…As seen from Figure 2, the BTPS measures perfectionism with three second-order factors and ten first-order facets. The original BTPS was adapted to Turkish by Kilmen and Arikan (2020). The factor structure of the BTPS was confirmed in the Turkish undergraduate student sample.…”
Section: Methodsmentioning
confidence: 91%
“…Although the results of Kilmen and Arikan’s study do not permit evaluating the BTPS’s cultural measurement invariance—because the data only contain the Turkish undergraduate student sample—they provide preliminary evidence, revealing that the BTPS facets have the same conceptual meaning in the Turkish sample. The results of Kilmen and Arikan (2020) showed that the BTPS can be used reliably to measure perfectionism in the Turkish sample. More details about facets were given in the introduction section (see Table 1).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is always advisable to investigate the psychometric properties of an instrument that has been translated into another language. In this instance, existing psychometric evidence attests generally to the sound psychometric properties of the original BTPS (e.g., Kilmen & Arikan, 2020) and the short form of the BTPS (Feher et al, 2020) and this includes research with older participants from Iran who completed the BTPS (see Besharat & Atari, 2017). However, the psychometric properties of the BTPS have not been evaluated in a sample of high school students from Iran.…”
Section: Introductionmentioning
confidence: 99%